The changing perception of animal welfare in cockfighting in relation to the tradition of «Un camarón» («One Shrimp») - Ramírez Pinedo, Ana Daniela (2024)
In this scientific paper, we will analyse the tradition «Un camarón» («One Shrimp»), by Ricardo Palma, and the cockfights described in it. The aim is to demonstrate the change in people’s social perception of animal abuse and well-being from the 19th century to the present day. Likewise, we will prove the lack of bioethics of cockfighting, emphasising how this practice violates the well-being of these animals. Furthermore, we will demonstrate the influence of Christian religion and culture on the reification of animals and how this has historically affected the recognition of their rights. Finally, we will discuss the importance of a bioethical approach to entertainment practices involving animals as a means of understanding the responsibility we have as thinking beings towards other non-human beings.